DEVELOPMENT OF ECONOMICS LEARNING THROUGH THE ANALYST CURRICULUM DATABASE IN ADVANCED ECONOMICS EDUCATION - Dwi Wulandari; Putra Hilmi Prayitno; Andi Basuki; Abdul Rahman Prasetyo; Ari Gunawan; Afis Baghiz Syafruddin (Dharmas Education Journal (DE_Journal), 2024)
Indonesia's significant economic development in recent decades, driven by various sectors, including information and communication technology, emphasizes the importance of broader economic education for students. However, a knowledge gap exists on how data-driven methodologies can be effectively applied in advanced economics curricula. This study uses a Research and Development (R&D)-based development methodology to design, develop, and evaluate a data analysis-based learning platform. The results show that this platform successfully meets very high validity criteria, with an average validation score of 86.67%, indicating the suitability of the material to learning objectives, data accuracy, and relevance to advanced economic concepts. In addition, the ease of navigation, the availability of technical support, and the quality of security and privacy are also rated excellent, reaching a score of 100%. These results confirm that the developed platform is academically relevant and capable of providing an interactive and safe learning experience for users. The implications of this study show that integrating data-based technology in economic learning can improve teaching effectiveness and student's understanding of complex economic concepts